2023
DOI: 10.21203/rs.3.rs-2817876/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ERK Hyperactivation Serves as a Unified Mechanism of Escape in Intrinsic and Acquired CDK4/6 Inhibitor Resistance in Acral Lentiginous Melanoma

Abstract: Patients with metastatic acral lentiginous melanoma (ALM) suffer worse outcomes relative to patients with other forms of cutaneous melanoma (CM), and do not benefit as well to approved melanoma therapies. Identification of cyclin-dependent kinase 4 and 6 (CDK4/6) pathway gene alterations in > 60% of ALMs has led to clinical trials of the CDK4/6 inhibitor (CDK4i/6i) palbociclib for ALM; however, median progression free survival with CDK4i/6i treatment was only 2.2 months, suggesting existence of resistance m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A study of 514 acral melanomas revealed that alterations in the CDK4 pathway were frequent and that these alterations promoted G1 to S cell cycle transition and tumor progression 15 . Recent studies have shown that combination treatment of CDK4/6 plus MEK inhibitors as first- and second-line therapy in patients with advanced AM 16 . Besides, we found that SM is higher CNV signal and lower T/NK cells, which suggests that SM may have strong characteristics of invasiveness and metastasis and have a worse prognosis, in agreement with the study of Holman BN et al 8 .…”
Section: Discussionmentioning
confidence: 99%
“…A study of 514 acral melanomas revealed that alterations in the CDK4 pathway were frequent and that these alterations promoted G1 to S cell cycle transition and tumor progression 15 . Recent studies have shown that combination treatment of CDK4/6 plus MEK inhibitors as first- and second-line therapy in patients with advanced AM 16 . Besides, we found that SM is higher CNV signal and lower T/NK cells, which suggests that SM may have strong characteristics of invasiveness and metastasis and have a worse prognosis, in agreement with the study of Holman BN et al 8 .…”
Section: Discussionmentioning
confidence: 99%
“…A study of 514 acral melanomas revealed that alterations in the CDK4 pathway were frequent and that these alterations promoted G1 to S cell cycle transition and tumor progression (Kong et al 2017). Recent studies have shown that combination treatment of CDK4/6 plus MEK inhibitors as rst-and second-line therapy in patients with advanced AM (Rebecca et al 2023). Besides, we found that SM is higher CNV signal and lower T/NK cells, which suggests that SM may have strong characteristics of invasiveness and metastasis and have a worse prognosis, in agreement with the study of Holman BN et al (Holman et al 2020).…”
Section: Discussionmentioning
confidence: 99%